Factors influencing infection risk in endurance athletes - Svendsen, I. S. (2016)
High training loads or prolonged bouts of acute exercise can increase susceptibility to opportunistic infections. Such infections, although generally medically innocuous, can have profound negative implications for athletic performance. This thesis presents a series of studies investigating which factors influence infection risk in athletes, as well as exploring potential strategies to maintain immunocompetence during heavy training. In Chapters 2 and 3, a large cohort of elite winter endurance athletes were followed over a number of years to determine patterns and frequency of illness in this population, and to identify training- and competition-related predictors of infection. Incidence rates and seasonal patterns of illness were found to be broadly similar to elite athletes from summer sports, and to the general population. Competition, air travel, greater day-to-day fluctuations in training load and lower performance level were significant predictors of illness. When high training loads are combined with insufficient recovery, athletes may become overreached or overtrained. Previous studies suggest that increasing carbohydrate intake can be an effective means of preventing overreaching during periods of intense training. In Chapter 4 we therefore investigated the efficacy of carbohydrate supplementation in reducing immune disturbances and symptoms of overreaching. The lower carbohydrate does (20 g/h during exercise) was found to be equally effective in preserving immunity and power output as the higher dose (60 g/h), with modest immune and performance changes observed in both groups following eight days of intensified training. Many athletes fail to ingest sufficient fluid to maintain euhydration during exercise. However, Chapter 5 found that moderate hypohydration, elicited by a 24 h period of fluid restriction, had little effect on immune responses to prolonged exercise. Altitude training is an important component of the training process of most of today s elite endurance athletes. Chapters 6 and 7 explored the effects of acute and prolonged hypoxic training on immunity. Despite a somewhat augmented stress hormone response to exercise in hypoxia, altitude training was found to have little negative effect on host defence, providing relative exercise intensity at altitude and sea-level was matched.